Latitudinal wave coupling of the stratosphere and mesosphere during the major stratospheric warming in 2003/2004 - Pancheva, D.; Mukhtarov, P.; Mitchell, N.J.; Andonov, B.; Merzlyakov, E.; Singer, W.; Murayama, Y.; Kawamura, S.; Xiong, J.; Wan, W.; Hocking, W.; Fritts, D.; et al. (München : European Geopyhsical Union, 2008)
The coupling of the dynamical regimes in the high- and low-latitude stratosphere and mesosphere during the major SSW in the Arctic winter of 2003/2004 has been studied. The UKMO zonal wind data were used to explore the latitudinal coupling in the stratosphere, while the coupling in the mesosphere was investigated by neutral wind measurements from eleven radars situated at high, high-middle and tropical latitudes. It was found that the inverse relationship between the variability of the zonal mean flows at high- and low-latitude stratosphere related to the SSW is produced by global-scale zonally symmetric waves. Their origin and other main features have been investigated in detail. Similar latitudinal dynamical coupling has been found for the mesosphere as well. Indirect evidence for the presence of zonally symmetric waves in the mesosphere has been found. publishedVersion